Staten Island, Tierra del Fuego: The largest breeding ground for southern rockhopper penguins? - Schiavini, Adrian Carlos Miguel (2000)
This paper provides new data on the location and size of Southern Rockhopper Penguin (Eudyptes chrysocome chrysocome) populations at Staten Island, Tierra del Fuego, Argentina, in view of population sizes previously reported for all the subspecies. Surveys were performed mainly during November-December 1998 and 1999.Mean nests were calculated in circular plots of 100 m2. Nest density was then extrapolated to the area occupied by nests, estimated from aerial pictures and through ground controls. Nests are distributed mainly on areas of tussock grass (Poa flabellata). Most of the nests were located in tightly-knit subcolonies. Nest density (+-SD) was estimated at102.5 (+-29.7) nests/100m2. Two localities, Cabo SanJuan and Bahia Franklin, together held 173,793 nests, 166,762 located in Bahia Franklin, extending over a radius of 3.2 km. Based on the reported population data for this subspecies, the global population for Southern Rockhopper Penguins is likely to be close to 636,000 pairs, with Staten Island holding 27.3% of the world population and Bahia Franklin alone holding 26.2% of the world population.The Southern Rockhopper Penguins of Staten Island were almost undisturbed and unknown during the 20th century. The population importance of Bahia Franklin for the species was not previously recognized, but it should now occupy  a central place of concern for the conservation of this species.